PROVERBIAL GENDER RELATIONSHIP IN DIFFERENT LANGUAGES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article is devoted to the analysis of the gender representation in proverbs and sayings in modern languages. There is no doubt that gender stereotypes existing in the society find their implicit or explicit expression in proverbs and sayings in modern languages, like English, Russian and Uzbek. This is due to the increasing role of women in the developing society and the ability of the language to reflect every important concept relevant for the existence and functioning of the language.